Simulation, analysis and optimisation of optical FSK systems - Ribeiro, Rui Fernando Gomes de Sousa (1999)
In this thesis, methods to detect frequency modulated digital signals are studied. In order to accomplish that goal, accurate models are developed for lasers based in bulk semiconductors and with quantum wells. The accuracy of these models is verified by comparison with measurements performed on lasers of experimental systems. (...)